HUBUNGAN PERSEPSI DENGAN HASIL BELAJAR SISWA PADA PEMBELAJARAN BIOLOGI MENGGUNAKAN MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) KELAS XI IPA DI SMA N 2 TAMBANG - Putri, Herizky Dwi Utami; Fauziah, Yuslim; Febrita, Elya (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the relationship of perception with student learning outcomes on biology learning using cooperative model Numbered Heads Together (NHT) class XI IPA in SMA N 2 Tambang. This research was conducted in September 2016. The sample in this research is 62 students of class XI IPAI and class XI IPAII academic year 2016/2017. Parameter of this research (1) student's perception toward applying cooperative learning model of typeed heads Together (NHT) with 5 indicators that are: attention, expectation, need, value system, and personality type, (2) student perception relation to application of cooperative learning model type NHT with students' Biology Science learning outcomes. Perceptual instruments are distributed through closed questionnaires, all valid questionnaire items and reliability, coefficiency of Alfa Cronbach reliability of 0, 810. The data collected was analyzed using SPSS version 20.00 for windows. The result of data analysis showed that students perception 4,00 (Good). There is a moderate positive correlation between perception and student learning outcomes (cognitive) on applying cooperative model of NHT type class XI IPA SMA N 2 Tambang with correlation coefficient (rhitung) 0,457. There is a weak positive relationship between perception and student learning outcomes (affective) on the application of NHT type cooperative model in class XI IPA SMA N 2 Tambang with correlation coefficient (rhitung) 0.385. There is a weak positive relationship between perception and student learning outcomes (psychomotor) on the application of NHT type cooperative model in class XI IPA SMA N 2 Tambang with correlation coefficient (rhitung) 0,278.Keywords: Student Perception, Learning Model Numbered Heads Together, learning outcomes